Relationship between chromatographic resolution and amide structure of chiral 2-hydroxy acids as O-(-)-menthoxycarbonylated diastereomeric derivatives for enantiomeric separation on achiral gas chromatography - Cha, Eunju; Kim, Sohee; Lee, Kang Mi; Kim, Ho Jun; Kim, Ki Hun; Kwon, Oh-Seung; Park, Ki Duk; Lee, Jaeick (ELSEVIER SCIENCE BV, 2016)
The relationship between chromatographic resolution and amide structure of chiral 2-hydroxy acids as O-(-)-menthoxycarbonylated diastereomeric derivatives on achiral gas chromatography was investigated to elucidate the best diastereomeric conformation for enantiomeric separation of chiral 2-hydroxy acids. Thirteen chiral 2-hydroxy acids were converted into nine different diastereomeric O-(-)-menthoxycarbonylated amide derivatives using the primary, secondary and cyclic amines to achieve complete enantiomeric separation through an achiral column. Each enantiomeric pair of 2-hydroxy acids as O-(-)-menthoxycarbonylated tert-butylamide derivatives was resolved on both the DB-5 and DB-17 columns with resolution factors ranging from 1.7 to 4.8 and 1.7 to 3.4, respectively. The results revealed that the structure of the amide moiety is shown to significantly affect chromatographic resolution. In addition, O-(-)-menthoxycarbonylated tert-butylamide derivatives were shown to be the best diastereomeric conformations for enantiomeric separation of 2-hydroxy acids. When comparing with our previous O-trifluoroacetylated(-)-menthyl ester derivatization method, the present results suggested that size differences between groups attached to the chiral center and conformational rigidity can have stronger effects on resolution than the distance between chiral centers. The elution of R- and S-stereoisomers was affected by the class of amine; i.e., primary, secondary, or cyclic, regardless of the substituents on the amine group, the structure of the 2-hydroxy acid, and the polarity of the column. (C) 2016 Elsevier B.V. All rights reserved.